Revitalisasi Pembelajaran Bangun Ruang melalui Kolaborasi Kontekstual RME dan STEAM - Irhadtanto, Boedy; Cuhanazriansyah, Muhammad Rinov; Pratama, Avita Widya (Papanda, 2025)
This study aims to examine the effectiveness of integrating Realistic Mathematics Education (RME) and the STEAM approach in enhancing students’ conceptual understanding of three-dimensional geometry at the Madrasah Tsanawiyah level. The research employed a qualitative approach with a case study design. The subjects were ninth-grade students at MTs Plus An-Nahdliyah. Data were collected through observation, interviews, and written tests, and analyzed using qualitative descriptive methods. The results indicate that the integration of RME and STEAM improves students’ conceptual understanding, spatial visualization, and critical and creative thinking skills. Furthermore, students showed increased learning motivation, mathematical communication, as well as collaboration and contextual problem-solving abilities. These findings suggest that RME-STEAM integration is an effective and relevant approach in modern mathematics education, particularly for teaching solid geometry.